An efficient proline-based homogeneous organocatalyst with recyclability. (4th January 2018) - Li, Qiang; Li, Yuan; Wang, Jingdong; Lin, Yingjie; Wei, Zhonglin; Duan, Haifeng; Yang, Qingbiao; Bai, Fuquan; Li, Yaoxian
Abstract : A homogeneous organocatalyst for asymmetric reduction of imines can be reused for several cycles through a self-assembly method using MNPs. Abstract : In this work, a homogeneous organocatalyst was developed for the asymmetric reduction of imines. This catalyst could be separated by cyclodextrin-modified Fe3 O4 @SiO2 magnetic nanoparticles and then released back into a fresh reaction for use more than seven times. Furthermore, a new catalytic mechanism was proposed and investigated through theoretical calculations.